Pengaruh Alokasi Dana Desa Terhadap Kesejahteraan Masyarakat (Studi: Desa di Kecamatan Tamiang Hulu, Kabupaten Aceh Tamiang) - Ainul Yusna Harahap (Forum Kerjasama Pendidikan Tinggi, 2021)
The objective of the research was to examine the Effect of Village Fund Allocation on Community Welfare. This research is using primary data with method of collecting data used was distributing questionnaires directly. Population in this research is the People in Tamiang Hulu Subdistrict, Alir Tani I Village, Alur Tani II, Pulau Tiga Plantation, Harum Sari and Wonosari. Statistical analysis used in this research is Multiple Linear Analysis using the help of SPSS (Statistical Package For The Social Science).The research method used is quantitative research. The results showed that the Allocation of Village Funds Has a Positive and Significant Effect on The Welfare of the Community.